Structural and Optical Properties of Gd2-xSmxO3 Nanorods. (2015) - Boopathi, G.; Raj, S. Gokul; Ramesh Kumar, G.; Mohan, R.
Abstract: Hexagonal phase Gd1-x Smx (OH)3 nanorods were successfully synthesized through precipitation technique. Cubic phase Gd2-x Smx O3 nanorods were obtained by dehydration of the corresponding Gd1-x Smx (OH)3 nanorods. The dopant percentage was optimized and maintained at 5 at.%. The hydroxide and oxide nanophosphors were systematically characterized by using powder X–ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy with energy dispersive X–ray (SEM/EDX), transmission electron microscopy (TEM) and photoluminescence (PL) spectrometry. The obtained results were discussed in detail.